Sistem Informasi Penjualan Pupuk Di Toko Mitra Tani Kota Pinang Berbasis Web - Wantika, Wantika (Universitas Labuhanbatu, 2020)
Writing This Final Project explain Sale of fertilizer in mitra tani kota pinang Web-based, where the application can be used to improve the efficiency and effectiveness in doing every job. And using Web Applications, as a language that is easy to understand. In writing using the programming language PhpMySQL, as the manufacture of dreamweaver sales data as a server to design the site. This Final Project is designed and make an application regarding the data of fertilizer sales in mitra tani quickly and accurately. The purpose of.